UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN BINI SIMPUR (DILENIA SP.), KEDEBIK (MELASTOMA SP.) DAN MENGKIRAI (TREMA ORIENTALIS) TERHADAP BAKTERI AEROMONAS HYDROPHILA - TIARA PUSPA ANJANI; KHADIJAH KHADIJAH; DWI FEBRIANTI; ARDIANSYAH KURNIAWAN; EVA LESTARI; OLIVIA KHANATI; DONA LISTA; LINDIATIKA LINDIATIKA (GANEC SWARA, 2023)
Bini simpur, kedebik, and mengkirai are plants that grow a lot on Bangka Island. This plant has benefits as herbal medicine. The novelty of this research is that the Bini Simpur, Kedebik and Kirai plants can be used to treat fish infected with Aeromonas hydrophila bacteria. This research method is to use disc diffusion. The results of the phytochemical screening test proved that the leaves of Bini Simpur, Kedebik and Kirai contain flavonoids, tannins and saponins. Kedebic plants can inhibit bacteria by 12.7 mm; bini simpur 11.55 mm; and approx 10.8 mm. Conclusion Bini Simpur, Kedebik, and Kirai leaf extracts have antibacterial activity against Aeromonas hydrophila.